Peran Pendidikan Tasawuf dalam Membentuk Generasi–Z yang Berkarakter Islami - Fikri Ihsan Ma’rifatulloh (UIN Sunan Gunung Djati Bandung, 2023)
As the Covid-19 pandemic worsens the mental health landscape as well as the character of Gen Z, we need to increase education to prevent these diverse negative effects of Gen Z from developing. One way is with tasawuf education. Where here the author has the aim of explaining how the role of Sufism education through the concepts of takhalli, tahalli, tajalli contributes to the development of the Islamic character of Generation Z. This research uses a qualitative approach by applying descriptive-analytical methods and data collection techniques. This research was conducted through social media studies and literature studies. The results of this study can be concluded that all forms of problems that are currently a challenge of the times that must be faced by Generation Z, one way is to apply Sufism education through the Takhalli concept, namely cleaning the heart. Tahalli, namely adorning oneself by getting used to good qualities, attitudes and deeds. And Tajalli, namely internalizing the divine qualities within.